Alopecia due to break dance. - Chieco, P. (European Journal of Pediatric Dermatology, 2015)
One of the most spectacular movements of the break dance is the turn upright with the head on the floor (“headspin”). Among the many traumatic lesions consequent to break dance there are also those dermatological, in particular hair loss as a result of repetitive trauma (1), but also a chronic inflammation of the scalp. It has also been reported a case of lichen planus pilaris (2) consequent to break dance. Alopecia due to break dance is characterized by hair thinning in the point of support and a more or less intense inflammatory reaction; the inflammation is sometimes visible to the naked eye, but it is better documented as fine scales with dermoscope; the inflammation of the dermis is probably responsible for the hair thinning. The presence of inflammation and thin hair allows its differentiation from other forms of traumatic alopecia as trichotillomania.